Positive electrode material for lithium ion secondary battery as well as positive electrode for lithium ion secondary battery and lithium ion secondary battery using the same
By coating the positive electrode active material particles with polyaniline or polypyrrole and ensuring a high N3 area ratio, the rate characteristics of lithium ion secondary batteries are maintained, addressing the deterioration issue in conventional coated batteries.
Patent Information
- Application Number
- JP2023092363
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-06-05
- Publication Date
- 2024-12-17
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Lithium ion secondary batteries using positive electrode active materials coated with conventional conductive polymers like polyaniline or polypyrrole experience significant deterioration in rate characteristics as the charge/discharge cycle progresses.
The positive electrode material includes polyaniline or polypyrrole coated on the surface of the active material particles, with a specific N3 area ratio of 0.08 or more in the N1s photoelectron spectrum, ensuring strong bonding and maintaining electron conduction paths during cycling.
This configuration prevents the deterioration of rate characteristics in lithium ion secondary batteries by maintaining electron conduction paths, even as the positive electrode active material particles expand and contract during charge/discharge cycles.
Smart Images

Figure 2024174506000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a positive electrode material for a lithium ion secondary battery, and a positive electrode for a lithium ion secondary battery and a lithium ion secondary battery each using the same. [Background technology]
[0002] In recent years, the spread of various electric vehicles is expected to help solve environmental and energy problems. Secondary batteries have been developed as on-board power sources for driving motors, etc., which hold the key to the spread of these electric vehicles. As secondary batteries, non-aqueous electrolyte secondary batteries such as lithium-ion secondary batteries, which are expected to have high energy density and high output, have been attracting attention.
[0003] Here, Patent Document 1 discloses a technique for preventing the progress of reaction of a positive electrode active material with moisture or carbon dioxide without adversely affecting the charge-discharge cycle durability of a lithium nickel composite oxide useful as a positive electrode active material for lithium ion secondary batteries. Specifically, Patent Document 1 proposes that the surface of a lithium nickel composite oxide particle is coated with about 0.1 to 5 mass % of a conductive polymer such as polypyrrole or polyaniline to prevent contact of the positive electrode active material with moisture or carbon dioxide. According to Patent Document 1, such a configuration makes it possible to handle the positive electrode active material in an air atmosphere without adversely affecting the battery characteristics (without causing a decrease in charge-discharge cycle durability). [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2020-191302 A Summary of the Invention [Problem to be solved by the invention]
[0005] According to the studies of the present inventors, it has been found that even when a lithium ion secondary battery is produced using a positive electrode active material having a configuration coated with a conductive polymer as disclosed in Patent Document 1, the rate characteristics of the battery may be significantly reduced as the charge-discharge cycle progresses.
[0006] Therefore, an object of the present invention is to provide a means for preventing a decrease in the rate characteristics of a lithium ion secondary battery that uses a positive electrode active material coated with a conductive polymer as the charge and discharge cycles proceed. [Means for solving the problem]
[0007] The present inventors have conducted extensive research to solve the above problems, and have found that the above problems can be solved by using polyaniline or polypyrrole as a conductive polymer and arranging a relatively large proportion of nitrogen atoms in the main chain of the conductive polymer that are in the form of radical cations on the surface of positive electrode active material particles, thereby completing the present invention.
[0008] One aspect of the present invention is a positive electrode material for a lithium ion secondary battery, comprising positive electrode active material particles and a conductive polymer made of polyaniline or polypyrrole arranged on the surface of the positive electrode active material particles. The positive electrode material is characterized in that, in an N1s photoelectron spectrum obtained by subjecting the surface of the positive electrode material to X-ray photoelectron spectroscopy (XPS), -N=, -NH- and -N ·+ When the areas of the peaks corresponding to H- are separated, N1, N2 and N3 are taken as N3, and the N3 area ratio, defined as N3 / (N1+N2+N3), is 0.08 or more. Effect of the Invention
[0009] According to the present invention, in a lithium ion secondary battery using a positive electrode active material having a configuration in which the positive electrode active material is coated with a conductive polymer, it is possible to prevent a decrease in the rate characteristics of the battery that accompanies the progress of charge and discharge cycles. [Brief description of the drawings]
[0010] [Figure 1] 1 is a cross-sectional view showing a schematic diagram of a stacked (flat) non-bipolar (internal parallel connection) secondary battery according to one embodiment of the present invention. [Diagram 2] FIG. 1 is a graph for explaining that the spectrum of nitrogen (N1s) when X-ray photoelectron spectroscopy (XPS) is performed on the surface of a positive electrode material according to an embodiment of the present invention can be separated into three peaks (N1 (-N=), N2 (-NH-), and N3 (-N +H-)) by peak separation analysis. [Diagram 3] This is a graph in which the rate characteristic retention rate (vertical axis) is calculated as the percentage [%] of the rate characteristic value immediately after charge / discharge cycling to the rate characteristic value immediately after cell conditioning, for the rate characteristics measured for the test cells of each Example and Comparative Example, and is plotted against the N3 area ratio (horizontal axis). DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0011] One embodiment of the present invention includes positive electrode active material particles and a conductive polymer made of polyaniline or polypyrrole arranged on a surface of the positive electrode active material particles, and the positive electrode active material includes -N=, -NH- and -N ·+ This is a positive electrode material for lithium ion secondary batteries, in which the N3 area ratio, defined as N3 / (N1+N2+N3), is 0.08 or more, where N1, N2 and N3 are the areas of the peaks when the peaks corresponding to H- are separated.
[0012] Hereinafter, the above-mentioned embodiment of the present invention will be described with reference to the drawings, but the technical scope of the present invention should be determined based on the claims and is not limited to the following embodiments. The dimensional ratios in the drawings are exaggerated for the convenience of explanation and may differ from the actual ratios. In this specification, "X to Y" indicating a range means "X or more and Y or less." Furthermore, unless otherwise specified, operations and measurements of physical properties are performed under conditions of room temperature (20 to 25°C) and relative humidity of 40 to 50% RH.
[0013] FIG. 1 is a cross-sectional view that illustrates a flat (laminated) non-bipolar (internal parallel connection) secondary battery (hereinafter also simply referred to as a "laminated secondary battery") according to one embodiment of the present invention.
[0014] As shown in Fig. 1, the stacked secondary battery 10a of this embodiment has a structure in which a substantially rectangular power generating element 21, in which a charge / discharge reaction actually proceeds, is sealed inside a laminate film 29. Here, the power generating element 21 has a configuration in which a positive electrode in which a positive electrode active material layer 13 is arranged on both sides of a positive electrode collector 11', an electrolyte layer 17 made of a separator containing an electrolytic solution, and a negative electrode in which a negative electrode active material layer 15 is arranged on both sides of a negative electrode collector 12 are laminated. Specifically, the positive electrode, the electrolyte layer, and the negative electrode are laminated in this order such that one positive electrode active material layer 13 and the adjacent negative electrode active material layer 15 face each other with the electrolyte layer 17 interposed therebetween.
[0015] As a result, the positive electrode, the electrolyte layer, and the negative electrode constitute one unit cell layer 19. Therefore, the stacked secondary battery 10a shown in FIG. 1 can be said to have a configuration in which a plurality of unit cell layers 19 are stacked and electrically connected in parallel. The positive electrode current collectors of the outermost layers located on both outermost layers of the power generating element 21 each have the positive electrode active material layer 13 disposed on only one side, but active material layers may be provided on both sides. That is, instead of using a current collector dedicated to the outermost layer with an active material layer provided on only one side, a current collector having active material layers on both sides may be used as the current collector of the outermost layer as it is. Also, by reversing the arrangement of the positive electrode and the negative electrode from FIG. 1, the outermost negative electrode current collector may be located on both outermost layers of the power generating element 21, and the negative electrode active material layer may be disposed on one or both sides of the outermost negative electrode current collector.
[0016] A positive electrode current collector 25 and a negative electrode current collector 27 that are electrically connected to the electrodes (positive and negative electrodes) are attached to the positive electrode current collector 11' and the negative electrode current collector 12, respectively, and are structured to be sandwiched between the ends of the laminate film 29 and led out of the laminate film 29. The positive electrode current collector 25 and the negative electrode current collector 27 may be attached to the positive electrode current collector 11' and the negative electrode current collector 12 of the electrodes by ultrasonic welding, resistance welding, or the like, respectively, via a positive electrode terminal lead and a negative electrode terminal lead (not shown) as necessary.
[0017] The main components of the stacked secondary battery according to this embodiment will be described below.
[0018] [Current collector] The current collector has a function of mediating the movement of electrons from the positive electrode active material layer and the negative electrode active material layer described later. There are no particular limitations on the material constituting the current collector. For example, metals and conductive resins can be used as the material constituting the current collector.
[0019] Specifically, examples of the metal include aluminum, nickel, iron, stainless steel, titanium, and copper. In addition to these, clad materials of nickel and aluminum, clad materials of copper and aluminum, and the like may be used. Also, a foil in which a metal surface is coated with aluminum may be used. Among them, aluminum, stainless steel, copper, and nickel are preferred from the viewpoints of electronic conductivity, battery operating potential, and adhesion of the negative electrode active material to the current collector by sputtering. In addition, examples of the resin having electrical conductivity include resins in which a conductive filler is added to a non-conductive polymer material.
[0020] The current collector may have a single layer structure made of a single material, or may have a laminate structure in which layers made of these materials are appropriately combined. From the viewpoint of reducing the weight of the current collector, it is preferable to include at least a conductive resin layer made of a resin having conductivity. In addition, from the viewpoint of blocking the movement of lithium ions between the single cell layers, a metal layer may be provided on a part of the current collector. Furthermore, if the positive electrode active material layer and the negative electrode active material layer described later are conductive by themselves and can perform a current collecting function, it is not necessary to use a current collector as a member separate from these electrode active material layers. In such a form, the positive electrode active material layer described later constitutes the positive electrode as it is, and the negative electrode active material layer described later constitutes the negative electrode as it is.
[0021] [Cathode active material layer] The positive electrode active material layer includes a positive electrode active material. In this embodiment, the positive electrode active material is included in the positive electrode active material layer in the form of the positive electrode material for lithium ion secondary batteries according to one embodiment of the present invention described above. As described above, the positive electrode material according to this embodiment includes positive electrode active material particles and a conductive polymer made of polyaniline or polypyrrole. The configuration of the positive electrode material according to this embodiment will be described below.
[0022] (Cathode active material) The positive electrode active material has a function of releasing ions such as lithium ions during charging and absorbing ions such as lithium ions during discharging. In the positive electrode material for lithium ion secondary batteries according to the present embodiment, the type of the positive electrode active material is not particularly limited. From the viewpoint of having a higher capacity, it is preferable that the positive electrode active material is made of the space group R3m. The positive electrode active material belonging to the space group R3m has a layered structure (layered rock salt structure) in which lithium atomic layers and transition metal atomic layers are alternately stacked. Therefore, by using such a positive electrode active material, the battery capacity of the lithium ion secondary battery can be improved.
[0023] Examples of the positive electrode active material belonging to the space group R3m include lithium-transition metal composite oxides such as LiCoO2, LiNiO2, LiMnO2, Li(Ni-Mn-Co)O2, Li(Ni-Co-Al)O2, and those in which a part of these transition metals is replaced by other elements. In some cases, two or more positive electrode active materials may be used in combination. More preferably, a composite oxide containing lithium and nickel is used, and even more preferably, Li(Ni-Mn-Co)O2 and those in which a part of these transition metals is replaced by other elements (hereinafter, also simply referred to as "NMC composite oxide") or Li(Ni-Co-Al)O2 and those in which a part of these transition metals is replaced by other elements (hereinafter, also simply referred to as "NCA composite oxide") is used, and particularly preferably, NMC composite oxide is used.
[0024] As described above, the NMC composite oxide and the NCA composite oxide also include composite oxides in which a part of the transition metal element is replaced by another metal element. In this case, the other elements include Al, Sn, Nb, Ti, Zr, Mg, W, P, V, Ca, Sr, Cr, Fe, B, Ga, In, Si, Mo, Y, V, Cu, Ag, Zn, etc., and are preferably Al, Sn, Nb, Ti, Zr, Mg, W, P, V, Ca, Sr, Cr, more preferably Al, Sn, Nb, Ti, Zr, Mg, P, Cr, and further preferably Al, Sn, Nb, Ti, Zr, Mg, from the viewpoint of improving cycle characteristics. However, the other metal elements that can replace the transition metal element of the NCA composite oxide are other than Al.
[0025] The lithium-transition metal composite oxide as the positive electrode active material particles has a high theoretical discharge capacity, and therefore is preferably represented by the general formula (1): Li x Ni a M b N c O2 (wherein x, a, b, c, and d satisfy 0.8≦x≦1.1, a+b+c=1, 0.33≦a≦0.95, 0.05≦b≦0.67, and 0≦c≦0.10. M is one or more elements selected from the group consisting of Mn and Co, and N is one or more elements selected from the group consisting of Al, Sn, Nb, Ti, Zr, and Mg). Here, x represents the atomic ratio of Li, a represents the atomic ratio of Ni, b represents the atomic ratio of M, and c represents the atomic ratio of N. The composition of each element can be measured, for example, by inductively coupled plasma (ICP) emission spectrometry.
[0026] From the viewpoint of realizing a higher discharge capacity, it is preferable that in the general formula (1), 0.80≦a≦0.95 (i.e., high nickel composite oxide). Here, as described above, the present inventors have found that even when a lithium ion secondary battery is produced using a positive electrode active material having a configuration coated with a conductive polymer as disclosed in Patent Document 1, the rate characteristics of the battery may be significantly reduced as the charge and discharge cycles proceed. And, it has also been found that such a decrease in the rate characteristics as the charge and discharge cycles proceed occurs more significantly when a high nickel composite oxide as described above is used. In this regard, according to the conventional technical common sense, since the conductive polymer is highly flexible and also shows an anchor effect due to the van der Waals force on the positive electrode active material particles, it was thought that peeling from the positive electrode active material particles would not occur. Contrary to such technical common sense, the decrease in durability of the rate characteristics as described above occurred because the positive electrode active material particles significantly contracted in the c-axis direction as a result of the H2→H3 transition of the high nickel composite oxide occurring around the cell voltage of 4.2 V during charging, and the conductive polymer peeled off from the positive electrode active material particles. For the above reasons, the positive electrode material according to the present embodiment is particularly useful when it contains high-nickel composite oxide as positive electrode active material particles.
[0027] In the positive electrode material according to this embodiment, the roughness factor of the positive electrode active material particles is preferably 3 or less. Here, the "roughness factor" is a parameter that is an index of the smoothness of the surface of the positive electrode active material particles, and is calculated as the ratio of the "BET specific surface area" to the "geometric specific surface area calculated from the average particle diameter" of the positive electrode active material particles (=BET specific surface area / geometric specific surface area) by the method described in JP 2023-15591 A. By controlling the roughness factor to 3 or less, the cycle durability and rate characteristics of the battery can be improved. The value of the roughness factor is preferably 2.7 or less, more preferably 2.4 or less. On the other hand, the lower limit of the roughness factor is 1 or more.
[0028] In the positive electrode material according to the present embodiment, the positive electrode active material particles preferably satisfy Y / X≦70 when the crystallite diameter calculated by the Williamson-Hall method is X (nm) and the average particle diameter (D50) calculated by the laser diffraction method is Y (nm). Here, Y / X is an index of the number of crystal grains constituting the positive electrode active material particles, and the smaller the value, the fewer the crystal grains constituting the particles. The crystallite diameter X (nm) and the average particle diameter (D50) are measured by the method described in JP 2023-15591 A. Y / X is more preferably 50 or less, and further preferably 40 or less. On the other hand, the lower limit of Y / X is 1 or more. When Y / X is within the above range, it is possible to further improve the cycle durability and rate characteristics of the battery. The value of the crystallite diameter (above X) of the positive electrode active material particles is not particularly limited, but is preferably 1 μm or more from the viewpoint of improving cycle durability. The average particle diameter (D50; Y above) of the positive electrode active material particles is not particularly limited, but from the viewpoint of achieving high output, it is preferably 1 to 10 μm, more preferably 1.5 to 6 μm, and even more preferably 2 to 5 μm.
[0029] Furthermore, the BET specific surface area S BET [m 2 / g] and the true specific gravity ρ [g / cm 3 ] to the following formula 1: [Formula 1] L s =6 / (ρ×S BET ) The equivalent particle size L is calculated according to s [μm] vs. the average particle size of the positive electrode active material particles (Y above) L D50 [μm] ratio value (L D50 / L s) is preferably 5 or less. The smaller this parameter is, the more monolithic the positive electrode active material is. Therefore, by making this value 5 or less, the positive electrode active material becomes more monolithic, and the cycle durability and thermal stability of the battery can be improved. The BET specific surface area of the positive electrode active material particles can be measured by performing measurement using nitrogen gas as the adsorption gas by the static capacitance method in accordance with "Method for measuring specific surface area of powder (solid) by gas adsorption" described in JIS Z8830:2013 (ISO 9277:2010), and analyzing by the multipoint method.
[0030] (Conductive Polymer) In the positive electrode material according to this embodiment, a conductive polymer made of polyaniline or polypyrrole is disposed on the surface of the positive electrode active material particles. Both polyaniline and polypyrrole may be disposed. The conductive polymer is disposed in a state of covering preferably 50% or more, more preferably 80% or more, even more preferably 90% or more, and particularly preferably 95% or more of the surface of the positive electrode active material particles. However, a conductive polymer other than polyaniline and polypyrrole may be further disposed on the surface of the positive electrode active material particles. However, the mass ratio of polyaniline and / or polypyrrole in the conductive polymer disposed on the surface of the positive electrode active material particles is preferably 80% by mass or more, more preferably 90% by mass or more, even more preferably 95% by mass or more, and particularly preferably 100% by mass.
[0031] Polyaniline (PANI) and polypyrrole (PPy) are conductive polymers that have the repeating structure represented by the following chemical formulas.
[0032] [ka]
[0033] As shown in the above chemical formula, both polyaniline (PANI) and polypyrrole (PPy) have nitrogen atoms in their main chains. Taking the nitrogen atoms in the main chain of polyaniline (PANI) as an example, these nitrogen atoms can exist in the following three states:
[0034] [ka]
[0035] Of the three states described above, N1 is a state in which the nitrogen atom forms an imino group -N=. N2 is a state in which the nitrogen atom forms a secondary amino group (-NH-) and has an unshared electron pair (lone pair). N3 is a state in which the nitrogen atom forms a secondary amino group (-NH-) and is a radical cation, and a positive charge and an unpaired electron exist on the nitrogen atom in addition to the three bonds. The present inventors have found that a positive electrode material that can prevent the rate characteristics of a battery from decreasing with the progress of charge and discharge cycles can be provided by setting the ratio of N3 to the total of N1 to N3 at a predetermined value or more for the state of nitrogen atoms in these conductive polymers arranged on the surface of the positive electrode active material particles, and have completed the present invention.
[0036] In this specification, as an index of the proportion of N3, the peak area corresponding to the chemical state of nitrogen (N1s) when X-ray photoelectron spectroscopy (XPS) is performed on the surface of the positive electrode material is used. The specific measurement method is described in the Examples section below.
[0037] The spectrum of nitrogen (N1s) obtained by the above measurement consists of three species (N1(-N=), N2(-NH-), and N3(-N ·+H-)) peaks, and the area of each peak can be calculated by peak separation analysis. Taking advantage of this, in the present invention, the value of N3 / (N1+N2+N3) calculated using the peak areas of each peak (respectively N1, N2, and N3) is defined as the N3 area ratio, and is used as an index of the proportion of N3. The binding energies corresponding to each peak are 398.5 eV (N1), 399.4 eV (N2), and 400.4 eV (N3), respectively.
[0038] The positive electrode material according to the present embodiment is characterized in that the N3 area ratio is 0.08 or more. The N3 area ratio is preferably 0.10 or more, more preferably 0.12 or more, even more preferably 0.18 or more, particularly preferably 0.21 or more, and most preferably 0.25 or more. There is no particular limit to the upper limit of the N3 area ratio, but it is usually 0.35 or less.
[0039] Here, the present inventors speculate that the mechanism by which the above-mentioned effect is achieved by setting the value of the N3 area ratio to 0.08 or more is as follows. That is, in a positive electrode material having a large N3 area ratio of 0.08 or more, the proportion of radical cations (N3) occupying the chemical state of nitrogen atoms contained in the conductive polymer is high, so that the electrostatic interaction (attractive force) between the conductive polymer and the negative charge of the oxygen atoms present on the surface of the positive electrode active material particles is also large, and it is considered that they are firmly attached. For this reason, the conductive polymer arranged (coated) on the surface of the positive electrode active material particles is not easily peeled off even by the expansion and contraction of the positive electrode active material particles with the progress of the charge and discharge cycle. As a result, it is considered that the electron conduction path to the positive electrode active material particles is maintained for a long period of time, which contributes to preventing the deterioration of the rate characteristics of the battery with the progress of the charge and discharge cycle. However, whether this mechanism is correct or incorrect does not affect the technical scope of the present invention.
[0040] In the positive electrode material according to the present embodiment, the average molecular weight of polyaniline and polypyrrole is not particularly limited, and conventionally known knowledge may be appropriately referred to. As an example, the weight average molecular weight (polystyrene equivalent) using gel permeation chromatography is 1,000 to 1,000,000, preferably 5,000 to 50,000, and more preferably 10,000 to 30,000. In the positive electrode material according to the present embodiment, the mass ratio of the conductive polymer consisting of polyaniline and / or polypyrrole to the total amount (100 mass%) of the positive electrode active material particles is not particularly limited, but from the viewpoint of further exerting the action and effect of the present invention, it is preferably 1 to 15 mass%, more preferably 1 to 10 mass%, more preferably 2 to 10 mass%, and even more preferably 5 to 10 mass%. In addition, when the conductive polymer contains both polyaniline and polypyrrole, the value of this mass ratio is calculated from the total amount of these.
[0041] (Method of manufacturing positive electrode material) A positive electrode material having the above-mentioned configuration can be obtained, for example, as described in the Examples section below, by mixing polyaniline or polypyrrole with positive electrode active material particles and disposing the conductive polymer on the surfaces of the positive electrode active material particles.
[0042] In some cases, a mixture of polyaniline or polypyrrole or its precursor and positive electrode active material particles can be baked under an inert gas atmosphere such as nitrogen gas or argon gas to obtain a positive electrode material having a conductive polymer disposed on the surface of the positive electrode active material particles. An example of the conductive polymer precursor is polyanthranilic acid, which is a precursor of polyaniline. The baking conditions cannot be unequivocally defined because they vary depending on the type of raw material or precursor of the conductive polymer. For example, when baking a mixture of polyaniline or polypyrrole and positive electrode active material particles, the baking conditions can be set at a temperature of about 100 to 150°C (preferably 120 to 140°C) for about 0.5 to 8 hours (preferably 1 to 5 hours). When baking a mixture of a precursor such as polyanthranilic acid and positive electrode active material particles, the baking conditions can be set at a temperature of about 220 to 340°C (preferably 240 to 320°C) for about 0.5 to 6 hours (preferably 1 to 5 hours). In this case, if the sintering conditions are made stricter (higher sintering temperature and / or longer sintering time), the above-mentioned N3 area ratio tends to be smaller. Therefore, if milder sintering conditions are selected, it is possible to manufacture a positive electrode material whose N3 area ratio satisfies the above-mentioned requirement without excessive trial and error.
[0043] The content of the positive electrode material in the positive electrode active material layer (the total amount when two or more types are contained) is not particularly limited, but is preferably 60 to 99 mass%, and more preferably 80 to 95 mass%, relative to 100 mass% of the total solid content of the positive electrode active material layer.
[0044] The positive electrode active material layer may further contain a conductive assistant, a binder, and the like in addition to the positive electrode active material.
[0045] (Conductive assistant) The conductive assistant has a function of forming an electronic conductive path (conductive passage) in the positive electrode active material layer. When such an electronic conductive path is formed in the positive electrode active material layer, the internal resistance of the battery can be reduced and the rate characteristics can be improved.
[0046] Examples of the conductive assistant include particulate carbon materials such as acetylene black, carbon black, channel black, thermal black, and Ketjen Black (registered trademark), and fibrous carbon materials such as carbon nanotubes (single-walled carbon nanotubes and multi-walled carbon nanotubes), carbon nanofibers, vapor-grown carbon fibers, electrospun carbon fibers, polyacrylonitrile-based carbon fibers, and pitch-based carbon fibers. Only one type of conductive assistant may be used alone, or two or more types may be used in combination.
[0047] The content of the conductive assistant that can be contained in the positive electrode active material layer (the total amount when two or more kinds are contained) is not particularly limited, but is preferably 0.5 to 10 mass %, and more preferably 1 to 5 mass %, relative to 100 mass % of the total solid content of the positive electrode active material layer.
[0048] (Binder) The optional binder used in the positive electrode active material layer is not particularly limited, but examples thereof include the following materials: Polybutylene terephthalate, polyethylene terephthalate, polyvinylidene fluoride (PVDF) (including compounds in which hydrogen atoms are replaced by other halogen elements), polyethylene, polypropylene, polymethylpentene, polybutene, polyether nitrile, polytetrafluoroethylene, polyacrylonitrile, polyimide, polyamide, ethylene-vinyl acetate copolymer, polyvinyl chloride, thermoplastic polymers such as styrene-butadiene rubber (SBR), ethylene-propylene-diene copolymer, styrene-butadiene-styrene block copolymer and its hydrogenated product, styrene-isoprene-styrene block copolymer and its hydrogenated product, tetrafluoroethylene-hexafluoropropylene copolymer (FEP), tetrafluoroethylene-perfluoroalkyl vinyl ether copolymer (PFA), ethylene-tetrafluoroethylene copolymer (ETFE), polychlorotrifluoroethylene (PCTFE), ethylene Examples of the fluororesin include vinylidene fluoride-based fluororubbers such as vinylidene fluoride-hexafluoropropylene-based fluororubber (VDF-HFP-based fluororubber), vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene-based fluororubber (VDF-HFP-TFE-based fluororubber), vinylidene fluoride-pentafluoropropylene-based fluororubber (VDF-PFP-based fluororubber), vinylidene fluoride-pentafluoropropylene-tetrafluoroethylene-based fluororubber (VDF-PFP-TFE-based fluororubber), vinylidene fluoride-perfluoromethylvinyl ether-tetrafluoroethylene-based fluororubber (VDF-PFMVE-TFE-based fluororubber), and vinylidene fluoride-chlorotrifluoroethylene-based fluororubber (VDF-CTFE-based fluororubber); and epoxy resins. Among these, polyvinylidene fluoride (PVDF), polyimide, styrene-butadiene rubber, carboxymethyl cellulose, polypropylene, polytetrafluoroethylene, polyacrylonitrile, and polyamide are preferable.
[0049] The content of the binder that can be contained in the positive electrode active material layer (the total amount when two or more types are contained) is not particularly limited, but is preferably 0.5 to 10 mass % and more preferably 1 to 5 mass % with respect to the total solid content of the positive electrode active material layer.
[0050] The thickness of the positive electrode active material layer is not particularly limited, and conventionally known knowledge about batteries can be appropriately referred to. For example, the thickness of the positive electrode active material layer is usually about 1 to 1000 μm, preferably 20 to 800 μm, more preferably 30 to 500 μm, and further preferably 40 to 200 μm. The larger the thickness of the positive electrode active material layer, the more the positive electrode active material can be retained to exhibit sufficient capacity (energy density). On the other hand, the smaller the thickness of the positive electrode active material layer, the more the discharge rate characteristics can be improved.
[0051] [Negative electrode active material layer] (Negative electrode active material) The negative electrode active material has a function of releasing ions such as lithium ions during discharge and absorbing ions such as lithium ions during charge.
[0052] Examples of the negative electrode active material include carbon materials such as graphite, soft carbon, and hard carbon, and lithium-transition metal composite oxides (e.g., Li4Ti5O 12 ), metal materials (tin, silicon), silicon-containing alloy-based negative electrode materials (e.g., Si 60 Sn 10 Ti 30 ), lithium alloy-based negative electrode materials (for example, lithium-tin alloy, lithium-silicon alloy, lithium-aluminum alloy, lithium-aluminum-manganese alloy, etc.). In some cases, two or more types of negative electrode active materials may be used in combination. From the viewpoint of capacity and output characteristics, silicon-containing alloy-based negative electrode materials, carbon materials, lithium-transition metal composite oxides, and lithium alloy-based negative electrode materials are preferably used as the negative electrode active materials. Of course, negative electrode active materials other than those mentioned above may be used.
[0053] Average particle diameter of the negative electrode active material (D 50) is not particularly limited, but from the viewpoint of high output, The thickness is preferably 1 to 100 μm, and more preferably 1 to 20 μm.
[0054] The content of the negative electrode active material in the negative electrode active material layer is, for example, 60% by mass or more and less than 100% by mass, preferably 80% by mass or more and 99.5% by mass or less, more preferably more than 95% by mass and 99.0% by mass or less, and even more preferably 97% by mass or more and 98.5% by mass or less, based on 100% by mass of the total solid content. If the content of the negative electrode active material is within the above range, both the battery capacity and the output characteristics can be achieved.
[0055] Furthermore, the negative electrode active material layer may further contain other additives, such as a conductive assistant and a binder, as described above for the positive electrode active material layer, as necessary.
[0056] The thickness of the negative electrode active material layer is not particularly limited, and the same thickness as that described above for the positive electrode active material layer can be adopted.
[0057] [Electrolyte layer] The electrolyte layer contains an electrolytic solution (liquid electrolyte) and preferably has a configuration in which a separator is impregnated with the electrolytic solution.
[0058] (electrolyte) The electrolyte has a function as a carrier of lithium ions. The electrolyte has a form in which a lithium salt is dissolved in a non-aqueous solvent. Preferably, the electrolyte is obtained by further adding a fluorine-containing carbonate to the non-aqueous solvent in which a lithium salt is dissolved.
[0059] The non-aqueous solvent is preferably one which can easily dissolve lithium salts, and examples of such non-aqueous solvents include chain carbonates such as dimethyl carbonate (DMC), diethyl carbonate (DEC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), and methyl ethyl carbonate (MEC); fluorine-containing chain carbonates in which some of the hydrogen atoms of these chain carbonates are substituted with fluorine atoms; ethylene carbonate (EC), propylene carbonate (PC), and butyl carbonate (BC). fluorine-containing cyclic carbonates in which some of the hydrogen atoms of these cyclic carbonates are substituted with fluorine atoms; methyl propionate (MP), methyl acetate (MA), methyl formate (MF), 4-methyldioxolane (4MeDOL), dioxolane (DOL), 2-methyltetrahydrofuran (2MeTHF), tetrahydrofuran (THF), dimethoxyethane (DME), dimethyl sulfoxide (DMSO), and γ-butyrolactone (GBL).
[0060] In particular, from the viewpoint of further improving the rapid charging characteristics and output characteristics, it is preferable that the non-aqueous solvent contains a chain carbonate, and it is more preferable that the non-aqueous solvent contains at least one selected from the group consisting of diethyl carbonate (DEC), ethyl methyl carbonate (EMC) and dimethyl carbonate (DMC).
[0061] Examples of the lithium salt include Li(FSO2)2N (lithium bis(fluorosulfonyl)imide; LiFSI), Li(C2F5SO2)2N, LiPF6, LiBF4, LiClO4, LiAsF6, and LiCF3SO3.
[0062] The concentration of the lithium salt in the non-aqueous solvent is preferably 0.1 to 3.0 mol / L, and more preferably 0.8 to 2.2 mol / L.
[0063] In addition, it is preferable that the electrolyte further contains a fluorine-containing carbonate such as a fluorine-containing cyclic carbonate or a fluorine-containing chain carbonate. By doing so, the battery can be operated at a high voltage. Even if the electrolyte is heated, the electrolyte can have excellent durability. In addition, these fluorine-containing carbonates form a protective film on the surface of the positive electrode active material, and can increase the voltage resistance of the positive electrode active material. In this case, as the fluorine-containing carbonate, fluorine-containing cyclic carbonates such as fluoroethylene carbonate (FEC), difluoroethylene carbonate, and 4-fluoropropylene carbonate; fluorine-containing chain carbonates such as ethyl trifluoromethyl carbonate, 2,2,2-trifluoroethyl methyl carbonate, and bis(2,2,2-trifluoroethyl) carbonate can be preferably used. The content of the fluorine-containing carbonate is not particularly limited. In a preferred embodiment, the electrolyte contains 0.5 to 10 mass% of the fluorine-containing carbonate, particularly fluoroethylene carbonate, based on the total amount of the finally obtained electrolyte. This makes it possible to obtain the above-mentioned effect more remarkably. When the electrolyte contains two or more kinds of fluorine-containing carbonates, the total amount is preferably within the above-mentioned range.
[0064] The electrolyte may further contain additives other than the above-mentioned components. Specific examples of such compounds include ethylene carbonate, vinylene carbonate, methylvinylene carbonate, dimethylvinylene carbonate, phenylvinylene carbonate, diphenylvinylene carbonate, ethylvinylene carbonate, diethylvinylene carbonate, vinylethylene carbonate, 1,2-divinylethylene carbonate, 1-methyl-1-vinylethylene carbonate, 1-methyl-2-vinylethylene carbonate, 1-ethyl-1-vinylethylene carbonate, 1-ethyl-2-vinylethylene carbonate, and 1-ethyl-2-vinylethylene carbonate. Examples of the additives include ethylene carbonate, vinyl vinylene carbonate, allyl ethylene carbonate, vinyloxymethyl ethylene carbonate, allyloxymethyl ethylene carbonate, acryloxymethyl ethylene carbonate, methacryloxymethyl ethylene carbonate, ethynyl ethylene carbonate, propargyl ethylene carbonate, ethynyloxymethyl ethylene carbonate, propargyl oxyethylene carbonate, methylene ethylene carbonate, and 1,1-dimethyl-2-methylene ethylene carbonate. These additives may be used alone or in combination of two or more. The amount of additive used in the electrolyte solution may be appropriately adjusted.
[0065] (Separator) The separator constituting the electrolyte layer has a function of retaining the electrolyte to ensure lithium ion conductivity between the positive electrode and the negative electrode, and also a function of acting as a partition between the positive electrode and the negative electrode.
[0066] The separator may be in the form of, for example, a porous sheet separator made of a polymer or fiber capable of absorbing and retaining the electrolyte, or a nonwoven fabric separator.
[0067] As the separator of the porous sheet made of polymer or fiber, for example, a microporous (microporous membrane) can be used. Specific forms of the porous sheet made of the polymer or fiber include, for example, polyolefins such as polyethylene (PE) and polypropylene (PP); laminates of a plurality of these laminates (for example, a laminate having a three-layer structure of PP / PE / PP), polyimide, aramid, hydrocarbon resins such as polyvinylidene fluoride-hexafluoropropylene (PVDF-HFP), glass fibers, etc., and microporous (microporous membrane) separators can be mentioned.
[0068] As the nonwoven fabric separator, conventionally known materials such as cotton, rayon, acetate, nylon, polyester; polyolefins such as PP and PE; polyimide, aramid, etc. may be used alone or in combination.
[0069] The thickness of the separator may be the same as that of the electrolyte layer, and is preferably 5 to 200 μm, and particularly preferably 10 to 100 μm.
[0070] Also, a separator in which a heat-resistant insulating layer is laminated on a porous substrate (separator with heat-resistant insulating layer) can be used as the separator. The heat-resistant insulating layer is a ceramic layer containing inorganic particles and a binder. The separator with heat-resistant insulating layer is one having high heat resistance with a melting point or thermal softening point of 150°C or higher, preferably 200°C or higher. By having a heat-resistant insulating layer, the internal stress of the separator that increases when the temperature rises is alleviated, so that a heat shrinkage suppression effect can be obtained. As a result, it is possible to prevent the induction of short circuits between the electrodes of the battery, resulting in a battery configuration in which performance deterioration due to temperature rise is unlikely to occur. In addition, by having a heat-resistant insulating layer, the mechanical strength of the separator with heat-resistant insulating layer is improved, and the separator is unlikely to break. Furthermore, due to the heat shrinkage suppression effect and high mechanical strength, the separator is unlikely to curl during the battery manufacturing process.
[0071] [Positive and negative current collectors] The material constituting the current collector plates (25, 27) is not particularly limited, and any known highly conductive material conventionally used as a current collector plate for a lithium ion secondary battery may be used. As the material constituting the current collector plates, for example, metal materials such as aluminum, copper, titanium, nickel, stainless steel (SUS), and alloys thereof are preferable. From the viewpoints of light weight, corrosion resistance, and high conductivity, aluminum and copper are more preferable, and aluminum is particularly preferable. The positive electrode current collector plate 25 and the negative electrode current collector plate 27 may be made of the same material or different materials.
[0072] The lithium ion secondary battery using the positive electrode material for lithium ion secondary batteries according to the present embodiment has excellent rate characteristics even after the progress of charge and discharge cycles. Therefore, the lithium ion secondary battery using the positive electrode material according to the present embodiment is suitably used as a driving power source for EVs and HEVs.
[0073] Although one embodiment of the positive electrode material for lithium ion secondary batteries has been described above, the present invention is not limited to the configuration described in the above embodiment, and can be appropriately modified based on the description of the claims.
[0074] For example, the type of battery to which the positive electrode material for lithium ion secondary batteries according to the present embodiment is applied includes a bipolar battery including a bipolar electrode having a positive electrode active material layer electrically bonded to one surface of a current collector and a negative electrode active material layer electrically bonded to the opposite surface of the current collector.
[0075] The following embodiments are also included within the scope of the present invention: a positive electrode material according to claim 1 having the features of claim 2; a positive electrode material according to claim 1 or 2 having the features of claim 3; a positive electrode material according to claim 3 having the features of claim 4; a positive electrode material according to any one of claims 1 to 4 having the features of claim 5; a positive electrode for a lithium ion secondary battery according to claim 6, comprising a positive electrode material according to any one of claims 1 to 5; and a lithium ion secondary battery according to claim 7, comprising a positive electrode according to claim 6. EXAMPLES
[0076] The present invention will be described in more detail below with reference to examples, although the technical scope of the present invention is not limited to the following examples.
[0077] <Production example of polyaniline (PANI) coated positive electrode material> [Production Example 1] First, polycrystalline NMC composite oxide (LiNi 0.80 Mn 0.10 Co 0.10 O2, average particle diameter (D50): 4000nm, crystal structure: space group R3m, L D50 = 12.4 μm, L s = 0.7 μm, L D50 / L s =17.7) was prepared.
[0078] On the other hand, a 1% by mass polyaniline (weight average molecular weight <20,000)-NMP (N-methyl-2-pyrrolidone) solution was prepared, mixed with the positive electrode active material, and then dried under reduced pressure at 80°C for 6 hours to remove the NMP, obtaining a dried material. This dried material was used as the polyaniline-coated positive electrode material of Production Example 1 (no post-treatment was performed). The amount of polyaniline added to 100% by mass of the positive electrode active material was 5% by mass. This positive electrode material was intended for use in Example 1, which will be described later.
[0079] [Production Example 2] First, as the positive electrode active material (2), a single crystal (monolithic) NMC composite oxide (LiNi 0.84 Mn 0.08 Co 0.08 O2, average particle diameter (D50): 4000nm, crystal structure: space group R3m, L D50 = 4.6 μm, L s = 1.8 μm, L D50 / L s =2.5) was prepared.
[0080] On the other hand, a 1% by mass polyaniline-NMP (N-methyl-2-pyrrolidone) solution was prepared and mixed with the positive electrode active material, and then the mixture was dried under reduced pressure at 80°C for 6 hours to remove the NMP, thereby obtaining a dried material. The amount of polyaniline added relative to 100% by mass of the positive electrode active material was 10% by mass. Next, the dried material was subjected to a post-treatment of baking at 130°C for 1 hour in a nitrogen atmosphere to produce a polyaniline-coated positive electrode material of Production Example 2. This positive electrode material was intended for use in Example 2, which will be described later.
[0081] [Production Example 3] First, as the positive electrode active material (3), a single crystal (monolithic) NMC composite oxide (LiNi 0.90 Mn 0.04 Co 0.06 O2, average particle diameter (D50): 4000nm, crystal structure: space group R3m, L D50 = 5.8 μm, L s = 1.4 μm, L D50 / L s =4.2) was prepared.
[0082] On the other hand, a 1% by mass polyaniline-NMP (N-methyl-2-pyrrolidone) solution was prepared, mixed with the positive electrode active material, and then dried under reduced pressure at 80°C for 6 hours to remove the NMP, thereby obtaining a dried material. The amount of polyaniline added to 100% by mass of the positive electrode active material was 2% by mass. Next, the dried material was subjected to a baking treatment for 8 hours at 130°C in a nitrogen atmosphere as a post-treatment, thereby producing a polyaniline-coated positive electrode material of Production Example 3. This positive electrode material is intended for use in Example 3 described later.
[0083] [Production Example 4] First, polycrystalline NMC composite oxide (LiNi 0.80 Mn 0.10 Co 0.10 O2, average particle size (D50): 4000 nm, crystal structure: space group R3m) were prepared.
[0084] On the other hand, a 1% by mass polyaniline-NMP (N-methyl-2-pyrrolidone) solution was prepared and mixed with the positive electrode active material, and then the mixture was dried under reduced pressure at 80°C for 6 hours to remove the NMP, thereby obtaining a dried material. The amount of polyaniline added relative to 100% by mass of the positive electrode active material was 6% by mass. Next, the dried material was subjected to a baking treatment for 4 hours at 180°C in a nitrogen atmosphere as a post-treatment, thereby producing a polyaniline-coated positive electrode material of Production Example 4. This positive electrode material is intended for use in Comparative Example 2 described later.
[0085] [Production Example 5] First, as the positive electrode active material (2), a single crystal (monolithic) NMC composite oxide (LiNi 0.84 Mn 0.08 Co 0.08 O2, average particle size (D50): 4000 nm, crystal structure: space group R3m) were prepared.
[0086] On the other hand, a 1% by mass polyaniline-NMP (N-methyl-2-pyrrolidone) solution was prepared and mixed with the positive electrode active material, and then the mixture was dried under reduced pressure at 80°C for 6 hours to remove the NMP, thereby obtaining a dried material. The amount of polyaniline added relative to 100% by mass of the positive electrode active material was 5% by mass. Next, the dried material was subjected to a baking treatment for 8 hours at 180°C in a nitrogen atmosphere as a post-treatment, thereby producing a polyaniline-coated positive electrode material of Production Example 5. This positive electrode material is intended for use in Comparative Example 3 described later.
[0087] <Production example of anthranilic acid-derived polyaniline (AA-derived PANI)-coated positive electrode material> [Production Example 6] First, polycrystalline NMC composite oxide (LiNi 0.80 Mn 0.10 Co 0.10 O2, average particle size (D50): 4000 nm, crystal structure: space group R3m) were prepared.
[0088] On the other hand, a 0.1M aqueous solution of ammonium peroxodisulfate ((NH4)2S2O8) was mixed with a 0.1M aqueous solution of anthranilic acid (2-aminobenzoic acid) in sulfuric acid and left at room temperature for 24 hours. Thereafter, the solid matter precipitated in the liquid was filtered, thoroughly washed with ion-exchanged water, and vacuum dried to obtain polyanthranilic acid. This polyanthranilic acid was dissolved in NMP, mixed with a positive electrode active material, and then dried under reduced pressure at 80°C for 6 hours to remove the NMP, thereby obtaining a dried product consisting of a mixture of polyanthranilic acid and a positive electrode active material. Next, the dried product was subjected to a baking treatment for 4 hours at 250°C in a nitrogen atmosphere as a post-treatment, thereby producing an anthranilic acid-derived polyaniline-coated positive electrode material of Production Example 6. The amount of polyanthranilic acid added was adjusted so that the amount of polyaniline mixed with respect to 100% by mass of the positive electrode active material was 15% by mass. This positive electrode material is for use in Example 5 described later.
[0089] [Production Example 7] First, polycrystalline NMC composite oxide (LiNi 0.84 Mn 0.06 Co 0.10 O2, average particle diameter (D50): 4000nm, crystal structure: space group R3m, L D50 = 9.3 μm, L s = 1.6 μm, L D50 / L s =5.9) was prepared.
[0090] On the other hand, polyanthranilic acid prepared in the same manner as in Production Example 6 was dissolved in NMP and mixed with the positive electrode active material, and then the mixture was dried under reduced pressure at 80°C for 6 hours to remove the NMP, thereby obtaining a dried product consisting of a mixture of polyanthranilic acid and the positive electrode active material. Next, the dried product was subjected to a post-treatment of baking at 300°C for 2 hours in a nitrogen atmosphere to produce the anthranilic acid-derived polyaniline-coated positive electrode material of Production Example 7. The amount of polyanthranilic acid added was adjusted so that the amount of polyaniline mixed relative to 100% by mass of the positive electrode active material was 0.8% by mass. This positive electrode material is for use in Example 7 described later.
[0091] [Production Example 8] First, as the positive electrode active material (2), a single crystal (monolithic) NMC composite oxide (LiNi 0.84 Mn 0.08 Co 0.08 O2, average particle size (D50): 4000 nm, crystal structure: space group R3m) were prepared.
[0092] On the other hand, polyanthranilic acid prepared in the same manner as in Production Example 6 was dissolved in NMP, mixed with the positive electrode active material, and then dried under reduced pressure at 80°C for 6 hours to remove the NMP, thereby obtaining a dried product consisting of a mixture of polyanthranilic acid and the positive electrode active material. Next, the dried product was subjected to a baking treatment for 2 hours at 400°C in a nitrogen atmosphere as a post-treatment, thereby producing an anthranilic acid-derived polyaniline-coated positive electrode material of Production Example 8. The amount of polyanthranilic acid added was adjusted so that the amount of polyaniline mixed relative to 100% by mass of the positive electrode active material was 15% by mass. This positive electrode material is for use in Comparative Example 6 described later.
[0093] [Production Example 9] First, as the positive electrode active material (3), a single crystal (monolithic) NMC composite oxide (LiNi 0.90 Mn 0.04 Co 0.06 O2, average particle size (D50): 4000 nm, crystal structure: space group R3m) were prepared.
[0094] On the other hand, polyanthranilic acid prepared in the same manner as in Production Example 6 was dissolved in NMP and mixed with the positive electrode active material, and then the mixture was dried under reduced pressure at 80°C for 6 hours to remove the NMP, thereby obtaining a dried product consisting of a mixture of polyanthranilic acid and the positive electrode active material. Next, the dried product was subjected to a baking treatment for 8 hours at 350°C in a nitrogen atmosphere as a post-treatment, thereby producing an anthranilic acid-derived polyaniline-coated positive electrode material of Production Example 9. The amount of polyanthranilic acid added was adjusted so that the amount of polyaniline mixed relative to 100% by mass of the positive electrode active material was 0.8% by mass. This positive electrode material is for use in Comparative Example 7 described later.
[0095] <Production example of polypyrrole (PPy) coated positive electrode material> [Production Example 10] First, polycrystalline NMC composite oxide (LiNi 0.84 Mn 0.06 Co 0.10 O2, average particle size (D50): 4000 nm, crystal structure: space group R3m) were prepared.
[0096] On the other hand, a 1% by mass polypyrrole-NMP (N-methyl-2-pyrrolidone) solution was prepared, mixed with the positive electrode active material, and then dried under reduced pressure at 80°C for 6 hours to remove the NMP, obtaining a dried material. This dried material was used as the polyaniline-coated positive electrode material of Production Example 10 (no post-treatment was performed). The amount of polypyrrole added to 100% by mass of the positive electrode active material was 6% by mass. This positive electrode material was intended for use in Example 4, which will be described later.
[0097] [Production Example 11] First, as the positive electrode active material (2), a single crystal (monolithic) NMC composite oxide (LiNi 0.84 Mn 0.08 Co 0.08 O2, average particle size (D50): 4000 nm, crystal structure: space group R3m) were prepared.
[0098] On the other hand, a 1% by mass polypyrrole-NMP (N-methyl-2-pyrrolidone) solution was prepared and mixed with the positive electrode active material, and then the mixture was dried under reduced pressure at 80°C for 6 hours to remove the NMP, and a dried material was obtained. The amount of polypyrrole added to 100% by mass of the positive electrode active material was 0.8% by mass. Next, the dried material was subjected to a baking treatment at 130°C for 1 hour in a nitrogen atmosphere as a post-treatment, to produce a polypyrrole-coated positive electrode material of Production Example 11. This positive electrode material is for use in Example 6, which will be described later.
[0099] [Production Example 12] First, polycrystalline NMC composite oxide (LiNi 0.80 Mn 0.10 Co 0.10 O2, average particle size (D50): 4000 nm, crystal structure: space group R3m) were prepared.
[0100] On the other hand, a 1% by mass polypyrrole-NMP (N-methyl-2-pyrrolidone) solution was prepared and mixed with the positive electrode active material, and then the mixture was dried under reduced pressure at 80°C for 6 hours to remove the NMP, thereby obtaining a dried material. The amount of polypyrrole added relative to 100% by mass of the positive electrode active material was 8% by mass. Next, the dried material was subjected to a baking treatment at 180°C for 4 hours in a nitrogen atmosphere as a post-treatment, thereby producing a polyaniline-coated positive electrode material of Production Example 12. This positive electrode material was intended for use in Comparative Example 4, which will be described later.
[0101] [Production Example 13] First, as the positive electrode active material (2), a single crystal (monolithic) NMC composite oxide (LiNi 0.84 Mn 0.08 Co 0.08 O2, average particle size (D50): 4000 nm, crystal structure: space group R3m) were prepared.
[0102] On the other hand, a 1% by mass polypyrrole-NMP (N-methyl-2-pyrrolidone) solution was prepared, mixed with the positive electrode active material, and then dried under reduced pressure at 80°C for 6 hours to remove the NMP and obtain a dried material. The amount of polypyrrole added relative to 100% by mass of the positive electrode active material was 4% by mass. Next, the dried material was subjected to a baking treatment for 8 hours at 180°C in a nitrogen atmosphere as a post-treatment to produce a polyaniline-coated positive electrode material of Production Example 13. This positive electrode material is intended for use in Comparative Example 5 described later.
[0103] <X-ray photoelectron spectroscopy (XPS) of the surface of positive electrode materials> The surface of the positive electrode material obtained in each of the above manufacturing examples was subjected to X-ray photoelectron spectroscopy (XPS) to analyze the chemical state of nitrogen (N1s) contained in the polyaniline or polypyrrole present on the surface of the positive electrode material. The measurement device and measurement conditions are as follows. X-ray photoelectron spectrometer (ULVAC-PHI VersaProbe III) ·X-ray source: Monochromated-Al-Kα ray 50W Photoelectron take-off angle: 45° -Measurement area: 200μmφ.
[0104] The spectrum of nitrogen (N1s) obtained by the above measurement consisted of three types: N1(-N=), N2(-NH-), and N3(-N ·+ H-)) peaks, and the areas of each peak can be calculated by peak separation analysis. Using this, the N3 area ratio, defined as N3 / (N1+N2+N3), was calculated from the peak areas of each peak (respectively designated N1, N2, and N3). The results are shown in Table 1 below.
[0105] Example of test cell preparation [Comparative Example 1] (Preparation of positive electrode) First, polycrystalline NMC composite oxide (LiNi 0.80 Mn 0.10 Co 0.10 O2, average particle size (D50): 4000 nm, crystal structure: space group R3m) were prepared.
[0106] Next, an appropriate amount of N-methyl-2-pyrrolidone (NMP) as a slurry viscosity adjusting solvent was added to the solid content consisting of 93 parts by mass of the positive electrode active material prepared above, 3 parts by mass of carbon black as a conductive assistant, and 4 parts by mass of polyvinylidene fluoride (PVdF) as a binder, and mixed to prepare a positive electrode active material slurry. Then, the obtained positive electrode active material slurry was applied to one side of an aluminum foil (thickness 20 μm) as a current collector using a doctor blade, and the coating film was dried on a hot plate at 80 ° C. for 1 hour. Then, the coating film was pressed, placed in a vacuum dryer, and dried under vacuum conditions at 130 ° C. for 8 hours to obtain a positive electrode in which a positive electrode active material layer (thickness 60 μm) with a porosity of 25% was formed on the current collector.
[0107] (Preparation of test cell) The prepared positive electrode was punched out to φ15mm, and the positive electrode active material layer was placed opposite to a metallic lithium foil (φ16mm) serving as a counter electrode, with a polypropylene separator placed between them. Next, the laminate of the positive electrode, separator, and counter electrode was placed on the bottom side of a coin cell (CR2032, material: stainless steel (SUS316)). Furthermore, a gasket was attached to maintain insulation between the electrodes, and the electrolyte was injected with a syringe. Then, the spring and spacer were laminated, and the upper side of the coin cell was overlapped and sealed by crimping to prepare a test cell (coin cell type lithium ion secondary battery). The electrolyte used was an electrolyte obtained by dissolving LiPF61mol / L in a mixed solvent of ethylene carbonate (EC) and diethyl carbonate (DEC) (volume ratio 30:70).
[0108] [Examples 1 to 7 and Comparative Examples 2 to 7] Test cells for each of the Examples and Comparative Examples were prepared in the same manner as in Comparative Example 1 described above, except that the positive electrode material prepared in the manufacturing example shown in Table 1 below was used instead of the positive electrode active material (1).
[0109] Evaluation of test cells The test cells prepared in the above examples and comparative examples were evaluated for rate characteristics before and after charge-discharge cycles by the following method. The following charge-discharge tests were performed using a charge-discharge tester (HJ-SD8, manufactured by Hokuto Denko Corporation) in a constant temperature bath set at 25°C.
[0110] The test cell was placed in a thermostatic chamber, and after the cell temperature became constant, the initial charge was performed with a constant current (CC) charge at 0.05C up to 4.3V, followed by a 0.1C constant current discharge down to 2.5V. Next, as cell conditioning, a set of 4.3V-0.1C constant current constant voltage (CCCV) charge (cutoff current 0.01C) and 0.1C constant current discharge (cutoff voltage 2.5V) was repeated three times. Note that a rest period of one hour was provided between discharge and charge and between charge and discharge.
[0111] Thereafter, a charge-discharge cycle consisting of 4.3 V-0.33 C-CCCV charging (cutoff current: 0.25 C) and 2.5 V-0.33 C-CC discharging was repeated 100 times.
[0112] Immediately after the above-mentioned cell conditioning and immediately after the charge / discharge cycle, the rate characteristics were evaluated by performing constant current (CC) discharge at 0.1C or 2.0C (cutoff voltage 2.5V) from a fully charged state by 4.3V-0.1C-CCCV charging (cutoff current 0.01C), and measuring the respective discharge capacity values (mAh / g). The percentage [%] of the discharge capacity value at 2.0C discharge relative to the discharge capacity value at 0.1C discharge was calculated as the rate characteristic. The results are shown in Table 1 below.
[0113] In addition, the rate characteristic retention rate was calculated as the percentage [%] of the rate characteristic value immediately after the charge-discharge cycle to the rate characteristic value immediately after the cell conditioning. The results are shown in Table 1 and Figure 3 below. Note that the higher the rate characteristic retention rate, the less likely the rate characteristic is to decrease even after the charge-discharge cycle has progressed.
[0114] [Table 1]
[0115] From the results shown in Table 1, it can be seen that according to the present invention, in a lithium ion secondary battery using a positive electrode active material having a configuration coated with a conductive polymer, by controlling the N3 area ratio to a value equal to or greater than a predetermined value, it is possible to prevent the rate characteristics of the battery from deteriorating as the charge / discharge cycle progresses. [Explanation of symbols]
[0116] 10a laminated secondary battery, 11' Positive electrode current collector 12 Negative electrode current collector 13 positive electrode active material layer, 15 negative electrode active material layer, 17 electrolyte layer, 19 cell layer, 21 Power generation elements, 25 Positive current collector (positive tab), 27 negative electrode current collector (negative electrode tab), 29 Laminating film.
Claims
1. Positive electrode active material particles; a conductive polymer made of polyaniline or polypyrrole arranged on the surface of the positive electrode active material particles; Including, In the N1s photoelectron spectrum obtained by subjecting the surface of the positive electrode material to X-ray photoelectron spectroscopy (XPS), -N=, -NH- and -N ・+ A positive electrode material for a lithium ion secondary battery, in which, when the areas of the peaks corresponding to H- are separated, are designated as N1, N2, and N3, the N3 area ratio defined as N3 / (N1+N2+N3) is 0.08 or more.
2. 2. The positive electrode material for lithium ion secondary batteries according to claim 1, wherein a mass ratio of the conductive polymer to a total amount (100 mass%) of the positive electrode active material particles is 1 to 15 mass%.
3. The positive electrode active material particles are represented by the general formula (1): Li x Ni a M b N c O 2 (In the formula, x, a, b, c, and d satisfy 0.8≦x≦1.1, a+b+c=1, 0.33≦a≦0.95, 0.05≦b≦0.67, and 0≦c≦0.
10.
3. The positive electrode material for lithium ion secondary batteries according to claim 1, having a composition represented by the formula: M is one or more elements selected from the group consisting of Mn and Co, and N is one or more elements selected from the group consisting of Al, Sn, Nb, Ti, Zr, and Mg.
4. The positive electrode material for a lithium ion secondary battery according to claim 3 , wherein the a satisfies 0.80≦a≦0.
95.
5. The BET specific surface area S of the positive electrode active material particles BET [m 2 / g] and the true specific gravity ρ [g / cm 3 ] to the following formula 1: [Formula 1] L s =6 / (ρ×S BET ) The equivalent particle diameter L calculated according to s [μm] to the D50 average particle diameter L D50 The ratio value of [μm] (L D50 / L s 4. The positive electrode material for a lithium ion secondary battery according to claim 3, wherein the molecular weight of the positive electrode material is 5 or less.
6. A positive electrode for a lithium ion secondary battery, comprising the positive electrode material for a lithium ion secondary battery according to claim 1 or 2.
7. A lithium ion secondary battery comprising the positive electrode for lithium ion secondary batteries according to claim 6.
Citation Information
Patent Citations
Coated lithium-nickel composite oxide particles and manufacturing method thereof
JP2020191302A
